Optimizing the design of coherently combined multicore fiber amplifiers - Steinkopff, Albrecht; Jauregui, Cesar; Aleshire, Christopher; Klenke, Arno; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
In this work we optimize the design of coherently-combined multicore fiber amplifiers. It has been shown that increasing the number of cores in such fibers helps to increase the combinable output power. However, in counter-pumped multicore fibers, thermal effects will finally lead to strong non-uniform mode-shrinking in each core. This, in turn, will result in a significant reduction of the combining efficiency. In this study we will examine the power and energy scaling potential for different pumping schemes and different fiber designs. To this purpose, a simulation tool is used that solves the laser rate equations taking into account the resulting temperature gradient and the transverse mode distortions caused by it. In the simulation co- and counter pumped multicore fibers with a square core arrangement and a core number ranging from 2×2 up to 10×10 will be considered. Moreover, we investigate the influence of the active core size in terms of thermal effects as well as the extractable output power and energy. Particular attention is paid to the mitigation of non-uniform mode-shrinking at the fiber end-facet. By comparing the co- and counter-pumped cases, we will show that a combinable output power of 26 kW (co-pump) instead of 14 kW (counter-pump) with a 10x10 MCF and 30 µm cores should be achievable.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coherent combining; Multicore fiber; Thermo-optical behavior